Avaliação da resistência à cavitação de revestimentos depositados pelo processo de soldagem MIG com posterior nitretação por plasma. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Erosion by cavitation is a phenomenon present in hydraulic components, where pressure variation occurs inside the fluid, generating cyclical wear mechanisms and promoting failure due to fatigue on the exposed surface. This wear is present in hydraulic rotor blades, especially in power generation turbines, being responsible for high maintenance costs and generation losses due to repair stops. As a material for the recovery of cavitated areas, austenitic stainless alloys stand out, especially those linked to Cobalt, however these alloys have high costs. In this way, studying wearresistant superalloys, as well as surface improvement processes, are presented as high-cost solutions. This work sought to compare the wear behavior of austenitic alloys, Inconel 625 and Cavitec, deposited by the MIG process with and without subsequent plasma nitriding on a CA6NM steel substrate. Deposition processes were carried out through MIG welding, followed by plasma nitriding, via PI3, and finally the evaluation of wear by cavitation according to ASTM G 32 Standard. Microstructure analyzes were carried out by optical microscopy and FEG, of chemical composition by EDS, of the phases present by the XRD and EBSD analysis. Tribological tests were carried out on the surfaces, and through FEG and EBSD monitoring and identification of wear mechanisms, phase transformation and crystallographic orientations were carried out during the cavitation test. The welded coatings showed low dilution, good cohesion, small regions of ZPD and low porosity, and their microstructure was mostly austenitic, organized in columnar grains with the presence of delta ferrite (δ) regions. The nitrided layers presented a cohesive appearance with average thickness for the Cavitec coating of 1.49 μm and for the Inconel 625 coating of 1.11 μm. Expanded austenite (S) phase was obtained, in addition to chromium nitrides (CrN) and iron nitrides (Fe4N), in small amounts. The nitriding process provided greater resistance to cavitation, and the samples remained for a longer period in the incubation stage. The nitrided layer acted to form a barrier to the premature onset of mass loss, presenting an aspect of superficial fracture as the initial damage. In the non-nitrided samples, the damage starts preferentially at the grain boundaries and slip bands, with the damage occurring more intensely in the Inconel 625 sample. to the cavitation process, mainly due to the energy expenditure during the martensitic transformation, presenting an intermediate phase γ → ε + α'. The grains with orientation <001> Rotated cube suffered greater wear, due to the direct passage γ → α', or to the wear directly in the austenitic phase. In general, the Cavitec samples absorbed a greater amount of energy from the cavitation process, characteristics are directly linked to the EFE of the material, favoring a transformation sequence γ → ε + α'. Nitriding proved to be an excellent alternative to increase the surface cavitation resistance.
Keywords: Cavitação; Erosão; Nitretação; Revestimentos; Aços Inoxidáveis; Cavitation; Erosion; Nitriding; Coating; Stainless Steels; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA